A METHOD TO REDUCE THE CURVATURE OF ARAI PLOTS PRODUCED DURING THELLIER PALAEOINTENSITY EXPERIMENTS PERFORMED ON MULTIDOMAIN GRAINS - Biggin A.J.; Böhnel H.N. (My University, 2003)
We highlight benefits resulting from a simple modification to the conventional Thellier–Coe (CTC) method of palaeointensity determination. A consideration of current theory pertaining to partial thermoremanence (pTRM) acquisition in pseudo-single (PSD) and multidomain (MD) grains is used to show that the reversed Thellier–Coe (RTC) method is expected to reduce the curvature of pTRM-NRM plots. Experimental data confirms that this is actually the case although there are some observed effects that are not accounted for by present theory. The RTC method is shown to be an improvement over the CTC method in the sense that it acts to reduce the palaeointensity overestimate produced when an experiment is abandoned below the Curie temperature because of alteration occurring. However, more work is necessary to verify its general applicability.
Keywords: magnetic domain; palaeointensity